Pengaruh Citra Merek, Harga, Dan Electronic Word Of Mouth (E-Wom) Terhadap Keputusan Pembelian Produk Sunscreen Azarine Pada Mahasiswa Febm Umrah - Maryana, Siska; Paramita, Bunga; Randa, Fradya (Program Studi Manajemen FEBM UMRAH, 2025)
This study aims to examine the influence of brand image, price, and electronic word of mouth (e-WOM) on purchasing decisions of Azarine sunscreen products among students of the Faculty of Economics and Maritime Business, Raja Ali Haji Maritime University. A quantitative approach was used using a survey method involving 93 respondents who had purchased or used the product. Data were analyzed using multiple linear regression. The results showed that partially price and e-WOM had a significant positive effect on purchasing decisions, while brand image did not have a significant effect. However, simultaneously, the three variables significantly influenced purchasing decisions. These findings can be strategic input for companies to improve their marketing strategies, especially in digital communication and brand positioning.